GLOBALIZATION OF PERUVIAN NON TRADITIONAL AGRICULTURAL PRODUCT TRADE WITH THE EUROPEAN UNION - Montoya Caceres, Lorena (2012)
Considering that all negotiation to sign a bilateral agreement with the European Union finished this year, this thesis project propose an strategy that will permit the growth of the exportation of non-traditional agricultural products from Peru to the European market. The strategy to define this proposal will be based on the analysis of the characteristics of both markets, their level of development and their export volumes in the last ten years. In addition there will be an analysis on their financial and investment methods with the purpose of promote an increment on the Peruvian exports.